2011
DOI: 10.1073/pnas.1018242108
|View full text |Cite
|
Sign up to set email alerts
|

MSI4/FVE interacts with CUL4–DDB1 and a PRC2-like complex to control epigenetic regulation of flowering time in Arabidopsis

Abstract: Flowering at the right time is crucial to ensure successful plant reproduction and seed yield and is dependent on both environmental and endogenous parameters. Among the different pathways that impinge on flowering, the autonomous pathway promotes floral transition independently of day length through the repression of the central flowering repressor FLOWERING LOCUS C (FLC). FLC blocks floral transition by repressing flowering time integrators such as FLOWERING LOCUS T (FT). MSI4/FVE is a key regulator of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
161
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(175 citation statements)
references
References 42 publications
12
161
0
Order By: Relevance
“…We found no global changes in H3K27 modification in CRBN-deficient CD4 + T cells (Fig. 3C), suggesting that CRBN does not regulate the global pattern of histone modifications in CD4 + T cells, similar to what has been reported about the regulation of histone modification by MSI4/FVE (12).…”
Section: Crbn Controls Histone Modification Of Kcna3supporting
confidence: 70%
See 2 more Smart Citations
“…We found no global changes in H3K27 modification in CRBN-deficient CD4 + T cells (Fig. 3C), suggesting that CRBN does not regulate the global pattern of histone modifications in CD4 + T cells, similar to what has been reported about the regulation of histone modification by MSI4/FVE (12).…”
Section: Crbn Controls Histone Modification Of Kcna3supporting
confidence: 70%
“…Moreover, we noticed that Cul4A and DDB1 fail to be recruited to the Kcna3 chromatin in the absence of CRBN. This finding is significant, because Cul4A and DDB1 are components of the CRBN E3 ubiquitin ligase complex that not only participate in ubiquitin ligase activity, but also are involved in H3K27 modifications, such as H3K27me3 and H3K27ac (12,15). We found that CRBN is responsible for EZH1 (a histone methyltransferase for H3K27 modification) recruitment to Kcna3 chromatin.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Alterations in PcG complex composition and association to chromatin may be beneficial as organisms undergo developmental transitions and respond to their environment, however (4,13). There is increasing evidence for regulation of PRC2 activity by posttranslational modifications of PcG proteins by E3 ubiquitin ligases (14,15). Here, we show that CLF SETdomain activity is regulated at the posttranslational level by UPWARD CURLY LEAF1 (UCL1), the F-box component of an E3 ligase that binds CLF and targets it for degradation via the ubiquitin-26S proteasome pathway.…”
mentioning
confidence: 99%
“…An earlier study demonstrated that FVE plays dual roles in flowering regulation and cold acclimation to provide evolutionary fitness to plants in sensing intermittent cold stress (41). In addition, FVE is also implicated in the photoperiod flowering pathway and is postulated to bind chromatin as a large protein complex of ∼1.0 MDa (54,55). Thus, it is likely that these versatile functions of FVE in environment-controlled flowering are achieved through specific interactions with distinct partners like HOS1 and CUL4-DDB1 (54,56).…”
Section: Discussionmentioning
confidence: 99%